Идентификация криминально значимых коллокаций в украиноязычных текстах - Хайрова, Нина Феликсовна; Узлов, Дмитрий Юрьевич (Військовий інститут Київського національного університету ім. Тараса Шевченка, 2013)
В работе предлагается двухэтапный метод идентификации именных коллокаций в криминалистически значимых текстах украинского языка. Метод включает логико-лингвистическую модель автоматического выделения в слабоструктурированном тексте именных словосочетаний и вероятностную модель определения совместимости слов словосочетания, предназначенную для повышения точности идентификации коллокаций.

This paper proposes a two-step method for identifying noun collocations in criminal meaningful texts in English. The method involves the logical-linguistic model for automatic selection noun phrases in semistructured text and probabilistic model for determining the compatibility of words phrases. The last model is intended to improve the accuracy of collocations identification.
Identification of criminal significant collocation in the Ukrainian-texts
Keywords: логико-лингвистическая модель; вероятностная модель; точность идентификации; грамматические структуры; criminal meaningful collocations; logical-linguistic model; probabilistic model; identification accuracy